2015
DOI: 10.5901/mjss.2015.v6n2p165
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Country of Origin on Relationship Quality: Empirical Evidence from Automotive Industry

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
0
5
0
2
Order By: Relevance
“…Azadi et al (2015) and Kumar et al (2013) confirmed that brand loyalty is the core influencing factor in the forming brand equity of the product. Some of the previous studies (Bahrinizadeh et al, 2014;Hilman and Hanaysha, 2015;Panda and Misra, 2014;Sanyal and Datta, 2011) also suggested that the effect of the country-of-origin image on brand loyalty is significant. Based on the literature, the following hypotheses are formulated: H a1 Country-of-origin image has a significant positive effect on brand loyalty.…”
Section: Brand Loyalty (Bl)mentioning
confidence: 92%
See 1 more Smart Citation
“…Azadi et al (2015) and Kumar et al (2013) confirmed that brand loyalty is the core influencing factor in the forming brand equity of the product. Some of the previous studies (Bahrinizadeh et al, 2014;Hilman and Hanaysha, 2015;Panda and Misra, 2014;Sanyal and Datta, 2011) also suggested that the effect of the country-of-origin image on brand loyalty is significant. Based on the literature, the following hypotheses are formulated: H a1 Country-of-origin image has a significant positive effect on brand loyalty.…”
Section: Brand Loyalty (Bl)mentioning
confidence: 92%
“…Some studies interpret the country image as consumers' perceptions regarding the quality of the product made in that country (Parameswaran and Yaprak, 1987;Shahin et al, 2012). While other studies consider country-of-origin as the beliefs about a country's industrialisation and national quality standard (Hilman and Hanaysha, 2015;Srikatanyoo and Gnoth, 2002). The country-of-origin image is related to the attributes, such as reputation of brand name, product design, appearance, variety, durability, technical advancement, trustworthiness, workmanship and status symbol (Hamzaoui and Merunka, 2006).…”
Section: Country-of-origin Image (Co)mentioning
confidence: 99%
“…3) Product Product quality is considered as an important part of enhancing the organization's competitive advantage [7]. Consequently, product quality is a matter of concern for the company.…”
Section: Corporate Imagementioning
confidence: 99%
“…Cada una de las partes que componen la organización es importante y afecta el proceso de aprendizaje. Ocurre de esta manera porque el talento y las competencias de cada una de las personas que integran la organización están involucradas en cada decisión y en cada proceso (Garzón Castrillón & Fisher, 2008 (Lestari, Thoyib, Zain, & Santoso, 2013).…”
Section: Introductionunclassified
“…Así, las tecnologías de información representan una herramienta imprescindible para fomentar los mecanismos de coordinación, colaboración y flujo de información, en un modelo de negocio con actores que pueden estar localizados en distintas partes del mundo y que pueden ejecutar procesos de manera sincronizada (Ochoa, 2012). La capacidad que tiene una empresa para desarrollar y diseñar nuevos productos y procesos, y también la capacidad que tiene una empresa para mejorar el conocimiento es la capacidad tecnológica de la empresa, que constituye un importante recurso para que una organización pueda lograr la innovación (Lestari et al, 2013).…”
Section: Introductionunclassified